علاقة استيعاب الطالبات للتصريف بقدرتهن على فهم نص القراءة في الصف العاشر بمعهد علو الهمة مارندال - Habibah Maulani, Habibah; Riyadi, Slamet; Lubis, Arbonas (Cahaya Ilmu Bangsa Institute, 2025)
The formulation of the problem in this study is whether there is a relationship between Tashrif Mastery and Reading Text Understanding in Class X Students of Ma'had Uluwwul Himmah Marendal? This study aims to see and find out the relationship between Tashrif Mastery and Reading Text Understanding in Class X Students of Ma'had Uluwwul Himmah Marendal. The method used in this study is a quantitative approach with a correlation method using statistical data analysis with the Spearman Brown formula to find research results. The results obtained are a relationship between Tashrif Mastery and Reading Text Understanding in Class X Students of Ma'had Uluwwul Himmah Marendal with a correlation value of 0.636 and shows a unidirectional relationship. So the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. And the conclusion is that there is a relationship between variable x and variable y.